(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the importance of studying verbs and tenses in modern Uzbek linguistics, the scope of work done in this field, and the problems to be solved. In particular, the views of the linguists A.G.G‘ulomov, A.Hojiyev, Sh.Shukurov, M.Sodikova, who conducted extensive research on the verb word group in the second half of the 20th century, their opinions about verbs and their publications scientific works are described. In addition, there is information about the scientific works of our scientists such as Sh.Rakhmatullayev, R.Rasulov, who worked in the field of verbs during the years of independence, as well as the issues studied by them in their books, and a number of PHD theses are considered.